Toxic effects of NH4+-N on embryonic development of Bufo gargarizans and Rana chensinensis. (September 2017) - Deng, Hongzhang; Chai, Lihong; Luo, Pingping; Zhou, Meimei; Nover, Daniel; Zhao, Xiaohong
Abstract: Although nitrogen fertilizer is commonly used worldwide, little information is currently available about NH 4 + -N toxicity on amphibians. This study determined the acute and chronic toxic effects of NH 4 + -N on two native Chinese amphibian species ( Bufo gargarizans and Rana chensinensis ), and compared the negative sensitivity of different embryos to NH 4 + -N. Static renewal aqueous exposures were performed using B. gargarizans and R. chensinensis embryos at Gosner stage 2 over 96 h. In terms of 96 h-LC50, B. gargarizans and R. chensinensis embryos had significantly different responses to NH 4 + -N, and the latter was more sensitive to NH 4 + -N than the former. In the chronic toxicity test, exposure to 10 mg L −1 NH 4 + -N or higher significantly decreased the hatching rate of embryos in both species. Significant increases in the abnormality rate of embryos at 50 mg L −1 NH 4 + -N or higher were observed and morphological abnormalities were characterized by axial flexures, yolk sac edema, and hyperplasia in both species. Additionally, the total length of embryos decreased in a dose-dependent manner after exposure to NH 4 + -N. The results indicate that NH 4 + -N exposure can increase abnormality and inhibit the hatching and development of embryos in B. gargarizans and R. chensinensis . Highlights: Nitrogen fertilizers can damage ecosystems health while benefiting crop production. The effects of NH4 + -N on two Chinese native amphibian species were compared. B. gargarizans and R. chensinensis embryos responded differently to NH4 + -N. NH4 + -N exposure may increase abnormality and inhibit embryo hatching and development. It has implication for fertilizer management and environmental standard for NH4 + -N.